Economic Integration Within the Concept of Sustainable Development - N. M. Keino; А. N. Sasinovich (Цифровая трансформация, 2021)
In this paper, the author analyzes economic integration, reveals its economic, social and environmental matters in the realm of sustainable development paradigm, traces the economic relations that arise in order to ensure environmental safety. The development of sustainable economic relations among countries, the deepening of the international division of labor, as one of the main tasks of environmental security. It is shown that integration interaction allows its participants to jointly solve the most acute economic, social and environmental problems. The result of the analysis of integration cooperation strategies is the allocation of the EU as a standard for regional economic and political interaction processes.